What is the international Monetary Fund? : (Revised 1996)(Reprinted 6/97). (Pamphlet Series; Pamphlet Series, No., 1996)
This paper explains the primary aim behind the founding of the IMF. The IMF is a cooperative institution that 181 countries have voluntarily joined because they see the advantage of consulting with one another in this forum to maintain a stable system of buying and selling their currencies so that payments in foreign money can take place between countries smoothly and without delay. The IMF lends money to members having trouble meeting financial obligations to other members, but only on condition that they undertake economic reforms to eliminate these difficulties for their own good and that of the entire membership.